Immunohistochemical assessment of the potential behavior of glandular odontogenic cyst and inflammatory periodontal cyst using E-cadherin and N-cadherin - Heba Ahmed Saleh; Dina M. Makawi; Asmaa Emad El-Din Mohamed Rashad (Beni-Suef University Journal of Basic and Applied Sciences, 2023)
Abstract Background This study is done to evaluate the immunohistochemical expression of E-cadherin and N-cadherin in glandular odontogenic cysts (GOC), inflammatory periodontal (IPDL) cysts, and dental follicles (DF), and if there is a correlation with their biological behavior GOC, IPDL cysts, and DF cases were collected and investigated by immunohistochemistry. The area percent of immunoexpressed markers was calculated by SPSS version 25. Results The statistical analysis revealed a clear, statistically significant difference between the studied groups regarding the area percentage of the two immune-expression markers (p value = 0.000). The highest area percentage of the mean value of E-cadherin was recorded in IPDL cysts group with the most negligible value recorded in the group of GOC. On the other hand, the highest area percentage of the mean value of N-cadherin was documented in the group of GOC with the least recorded value was noted in the group of DF. Conclusion We noted that the cadherin switch mechanism in the epithelial lining of odontogenic cysts is a critical step in the epithelial mesenchymal transition process which may associates with clinical behavior and may also impact the mode of treatment.